Measurements of top quark spin observables in tt⎯⎯ events using dilepton final states in s√=8 TeV pp collisions with the ATLAS detector - Aad, G. (2016)
Measurements of top quark spin observables in t t  ̄ events are presented based on 20.2 fb −1√ of s = 8 TeV proton?proton collisions recorded with the ATLAS detector at the LHC.The analysis is performed in the dilepton final state, characterised by the presence of twoisolated leptons (electrons or muons). There are 15 observables, each sensitive to a differentcoefficient of the spin density matrix of t t  ̄ production, which are measured independently. Tenof these observables are measured for the first time. All of them are corrected for detectorresolution and acceptance effects back to the parton and stable-particle levels. The measuredvalues of the observables at parton level are compared to Standard Model predictions at next-to-leading order in QCD. The corrected distributions at stable-particle level are presentedand the means of the distributions are compared to Monte Carlo predictions. No significantdeviation from the Standard Model is observed for any observable.